ANOMALI BANDWAGON EFFECT DAN MOMENTUM PARTAI POLITIK MERAIH SUARA PADA PEMILU 2024 - Sabarudin, Didin (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2024)
The 2024 presidential and legislative elections show anomalies in the vote results. Prabowo Subianto won the Presidential seat for the 2024-2029 period with a majority vote that dominated 36 provinces out of 38 provinces in Indonesia, so it did not have a significant impact on his political party, namely Gerindra obtained a majority of legislative seats, even dropping to third place compared to the 2019 election which was in second place. The personal impression of the President-elect did not have any impact even though the support from survey institutions and various media platforms became a looking-glass effect for the blessings of electoral politics for the Gerindra party. The electoral impact obtained by other parties from those who supported and did not support the President, increased significantly by double digits from the previous election. The article in this study uses an exploratory qualitative method with a case type, where the bandwagon effect of the Presidential election supported by horse-race journalism contributes or does not contribute to political parties' vote acquisition in understanding the natural social context phenomenon on political party relations, elections, and their subsequent impacts. The media and survey institutions with the various channels and platforms they use play a key role in post-reform polls with the results becoming a reference for the public to see the level of electability of presidential and legislative candidates, especially for young people as the majority of voters who reach 55% of the voting population. In fact, with various methods, they can increase vote acquisition, change election results through their multiple skills, and help their candidates defeat their competitors so that in this context survey institutions become business entities with high pay rates.